(untitled) (Delta Medical College Journal, 2024)
Background: Different studies support the utilization of risk-assessment scoring systems in quantifying individual’s risk for developing type 2 diabetes mellitus (T2DM). Thus, a simple risk-assessment scoring system for early screening of T2DM among Bangladeshi adults would be beneficial to identify the high-risk adults and thus taking adequate preventive measures in combating DM. Objective: The purpose of the study was to calculate the risk assessment score for developing type 2 DM among Bangladeshi adults using IDRS (Indian Diabetes Risk Score) tool and to assess the association of different risk factors of IDRS tool with the risk score. Materials and method: The cross sectional observational study was conducted among randomly sampled 482 adult Bangladeshi male and female subjects. The study population consisted of non-diabetic adults visiting the outpatient department (OPD) of Medicine, MARKS Medical College & Hospital, a tertiary care hospital in Dhaka, Bangladesh, from June 2018 to May 2019. A Semi-structured questionnaire consisting of demographic characteristics, risk factor profile of Indian Diabetes Risk Score (IDRS) was used. All the participants were assessed and categorized as high (IDRS ≥60), moderate (IDRS 30-50) and low risk (IDRS <30) based on the risk score of IDRS questionnaire. Data were entered and analyzed in SPSS. Results: Out of 482 subjects, female were 53.3%. The Mean (±SD) age of the study subjects was 38.92±1.12 years. According to IDRS score, 50.4% of the study subjects were at moderate risk and 37.3% were at high risk of developing diabetes; (p<0.05). The mean IDRS was significantly higher among female than male subjects (p<0.001). A statistically significant association of diabetes risk with different age group, waist circumference, level of exercise and positive family history for diabetes were seen. Conclusion: About 88% of the study subjects were at moderate to high risk of having diabetes, hence screening for risk factors is of utmost importance so that interventions can be initiated at an early stage. Delta Med Col J. Jan 2021;9(1):9-16